The Two Personae of Silvia Falsaperla - Davies, Adriana A. (Italian Canadiana, 2025)
Silvia Falsaperla immigrated to Toronto with her family at the end of 1965 at the age of seven from Catania, Sicily. At the age of seventeen, she began to write poetry and came under the influence of the League of Canadian Poets (LCP). She attended the University of Toronto and obtained a BA with an English major. The companion volumes The Garden of Kolymbethra and Other Poems and Stories of Sicily (2024) and Persephone’s Summer (2025) represent the totality of her vision and serve as a summation of her encounter with her family’s past in Italy and her life in Canada. She thus has a “Canadian” persona and an “Italian” persona. Her key themes are memory, myth, and homecoming, which she explores in sensual lyric poetry. In the short stories in The Garden of Kolymbethra, Falsaperla also paints word pictures of contemporary Catania, her home city.